2023
DOI: 10.1371/journal.pone.0280882
|View full text |Cite
|
Sign up to set email alerts
|

Post-discharge quality of life of COVID-19 patients at 1-month follow-up: A cross-sectional study in the largest tertiary care hospital of Bangladesh

Abstract: There is increasing evidence of the post-COVID-19 suffering and decreased quality of life in the COVID-19 patients. This study aimed to assess the quality of life and associated factors of COVID-19 patients at one month after discharge from the hospital. This was a cross-sectional study that was conducted at the post-covid clinic of Dhaka Medical College Hospital (DMCH) where RT–PCR-confirmed adult COVID-19 recovered patients were enrolled one month after discharge from the same hospital. They were consecutive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 24 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…However, in the second survey, the percentage of participants who experienced anxiety did not decrease significantly. Some studies have yielded similar results [30,[34][35][36]. Hoque et al [35] reported that symptoms of COVID-19 could affect the quality of life and emotional well-being of patients who have recovered from COVID-19.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…However, in the second survey, the percentage of participants who experienced anxiety did not decrease significantly. Some studies have yielded similar results [30,[34][35][36]. Hoque et al [35] reported that symptoms of COVID-19 could affect the quality of life and emotional well-being of patients who have recovered from COVID-19.…”
Section: Discussionmentioning
confidence: 81%
“…Some studies have yielded similar results [30,[34][35][36]. Hoque et al [35] reported that symptoms of COVID-19 could affect the quality of life and emotional well-being of patients who have recovered from COVID-19. Similarly, van der Sar-van der Brugge et al [38] reported that respiratory function could affect the quality of life and emotional well-being of individuals who have recovered from COVID-19.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation